A fábrica é escola. Práticas sociais e educativas de empresários e trabalhadores. - Gigante, Moacir (2003)
Education is usually treated from institutional, formal and schooling aspects. In this study however, education is investigated as a social work practice in the factory. The working day-to-day life of shoe factory workers in the city of Franca-SP is taken as the starting point. However, this is put in the context of relationships between historical capitalism and the historicity of the training in competencies for craftsmanship, manufacturing and industry, be it in general, in other manufacturing sectors, or be it in the specific context of the profession of shoemaker. Daily and oral history of workers are studied; the unique experience of each one of the collaborators in the research is the support base for the reflection and analysis on work and competencies training for work. Education for work is therefore studied: informal education, within the worker traditions, as well as institutional-scholarly education. Education as informal-professional, or institutionalscholarly is differently obtained and is differently destined for different functions and different social groups within the factory, a fact that accentuates and reinforces social stratifications. The creation of work competencies in the shoe factories is peculiarly associated, at each historical moment, with the very manner of organizing work routines. This fact implies a necessity for the comprehension of the real functions of formal education. This work contributes not only to the comprehension of the educational process and of the maintenance and extinction of the work competencies of footwear industry workers, but also to the comprehension of the aims of institutional education, in the past as well as in present society.